Гуси-лебеди: [русская народная сказка : для детей дошкольного возраста] (Проф-Пресс, 2016)
Экземпляры: ф.12 (20161212) / Инвентарный номер: 48774 / Цена: 36.00 / Сис.шифр: Д / Авт.знак: Г 96 / ГРНТИ: 17.82.93 / ББК: 82.3(2)